HYDROTHERMAL DIAMOND ANVIL CELL FOR XAFS STUDIES OF FIRST-ROW TRANSITION ELEMENTS IN AQUEOUS SOLUTION UP TO SUPERCRITICAL CONDITIONS - Bassett W.A.; Anderson A.J.; Mayanovic R.A.; Chou I.M. (My University, 2000)
A hydrothermal diamond anvil cell (HDAC) has been modified by drilling holes with a laser to within 150 μm of the anvil face to minimize the loss of X-rays due to absorption and scatter by diamond. This modification enables acquisition of K-edge X-ray absorption fine structure (XAFS) spectra from first-row transition metal ions in aqueous solutions at temperatures ranging from 25°C to 660°C and pressures up to 800 MPa. These pressure-temperature (P-T) conditions are more than sufficient for carrying out experimental measurements that can provide data valuable in the interpretation of fluid inclusions in minerals found in ore-forming hydrothermal systems as well as other important lithospheric processes involving water.
Keywords: X-RAY ABSORPTION; HIGH PRESSURE; ZINC CHLORIDE; DIAMOND ANVIL CELL; STRUCTURE OF SOLUTIONS; METAL-CHLORIDE COMPLEXES; SUPERCRITICAL AQUEOUS SOLUTIONS